2023
DOI: 10.1093/jas/skad112
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous fibrolytic enzymes promoted energy and nitrogen utilization and decreased CH4 emission per unit dry matter intake of tan sheep grazed a typical steppe by enhancing nutrient digestibility on China loess plateau

Abstract: Exogenous fibrolytic enzyme (EFE) products in ruminant nutrition may be an important alternative to meet the increased demands for animal products in the future with reduced environmental impacts. This study aimed to evaluate the dose response of EFE supplementation on the nutrient digestibility, nitrogen and energy utilization, and methane (CH4) emissions of Tan sheep grazed in summer and winter. A total of 20 Tan wether sheep with an initial body weight of 23.17 ± 0.24 kg were used in a randomized complete b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
2
0
0
Order By: Relevance
“…This may partially explain why, without changes in methanogenic archaea abundancy, the M-E reduced the intensity of methane emissions. Similar results have been reported in growing finishing lambs with exogenous fibrolytic enzymes in the intensity expressed per kg DM intake [74].…”
Section: Discussionsupporting
confidence: 89%
“…This may partially explain why, without changes in methanogenic archaea abundancy, the M-E reduced the intensity of methane emissions. Similar results have been reported in growing finishing lambs with exogenous fibrolytic enzymes in the intensity expressed per kg DM intake [74].…”
Section: Discussionsupporting
confidence: 89%
“…Sakita fed an fibrolytic enzyme product to growing lambs which increased their dietary digestible energy and ADF digestibility ( 8 ). Similar results were reported by Shi et al ( 9 ). Moreover, numerous studies have shown that supplementing dairy cow diets with enzymes can improve lactation performance ( 10–12 ).…”
Section: Introductionsupporting
confidence: 92%